Peran Pesantren dan Surau dalam Dakwah Islam di Indonesia - Panji Putrawan Makalalag; Rizky Amalia (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2025)
Pesantren and surau are traditional Islamic educational institutions that play an important role in the spread of Islam in Indonesia. Pesantren, which developed extensively in Java, integrate religious education and community development through boarding schools and direct guidance from kyai. During the Walisongo period, pesantren became centers for da'wah, education, and training for Islamic missionaries. Despite facing challenges during the Dutch and Japanese colonial periods, pesantren continued to contribute to education and the struggle for independence. In the modern era, pesantren have adapted to the demands of the times without abandoning traditional values. Surau, which developed in Sumatra, originally functioned as places of Hindu-Buddhist worship. After Islam entered the region, surau transformed into centers of Islamic education and spirituality. Surau played an important role in non-formal education through halaqoh methods, Quranic teaching, book studies, and tarekat practices. These institutions not only spread Islamic teachings but also preserved local cultural values, shaping the religious and civilized character of the Minangkabau people. Through a combination of educational, social, and spiritual functions, pesantren and surau have become important pillars in the development of Islamic society in Indonesia. Both institutions remain relevant in the era of globalization by preserving traditions while innovating to respond to the challenges of the times. Pesantren dan surau merupakan institusi pendidikan Islam tradisional yang memainkan peran penting dalam penyebaran Islam di Indonesia. Pesantren, yang banyak berkembang di Jawa, mengintegrasikan pendidikan agama dan pengembangan komunitas melalui asrama dan bimbingan langsung oleh kyai. Pada masa Walisongo, pesantren menjadi pusat dakwah, pendidikan, dan pelatihan kader penyebar agama Islam. Meskipun menghadapi tantangan selama penjajahan Belanda dan Jepang, pesantren terus berkontribusi dalam pendidikan dan perjuangan kemerdekaan. Di era modern, pesantren beradaptasi dengan tuntutan zaman tanpa meninggalkan nilai-nilai tradisional. Sedangkan surau, yang berkembang di Sumatera, awalnya berfungsi sebagai tempat ibadah Hindu-Buddha. Setelah Islam masuk, surau bertransformasi menjadi pusat pendidikan dan spiritualitas Islam. Surau memainkan peran penting dalam pendidikan nonformal melalui metode halaqoh, pengajaran Al-Qur'an, kajian kitab, dan praktek tarekat. Institusi ini tidak hanya menyebarkan ajaran Islam tetapi juga melestarikan nilai-nilai budaya lokal, membentuk karakter masyarakat Minangkabau yang religius dan beradab. Melalui kombinasi fungsi-fungsi pendidikan, sosial, dan spiritual, pesantren dan surau telah menjadi pilar penting dalam pengembangan masyarakat Islam di Indonesia. Kedua lembaga ini terus relevan di era globalisasi dengan mempertahankan tradisi sambil berinovasi untuk menjawab tantangan zaman.